Eloquence and reason creating a First Amendment culture - Tsai, Robert L., 1971- (New Haven, Conn. ; London : Yale University Press, 2008)
This provocative book presents a theory of the First Amendment's development. It reveals the social and institutional processes through which foundational ideas are generated and defends a cultural role for the courts.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: United States; Freedom of speech -- United States; Law; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general